The adoption of the multidimensional poverty index in developing Asia: implications for social program targeting and inequality reduction - Hlasny, Vladimir; Asadullah, M Niaz; Sabra, Alia (Penerbit Universiti Kebangsaan Malaysia, 2022)
The size and effectiveness of government expenditure is widely acknowledged as critical for global inequality reduction and achieving the Sustainable Development Goals (SDGs) by 2030. Yet, in addition to fiscal limits, governments in poor countries face a host of administrative constraints for effective targeting of social spending. Similar governance deficits also affect manyAsian middle-income countries. It is in this context that this paper revisits the call for countries to embrace multidimensional poverty and inequality instruments in poverty program planning and implementation throughout developing Asia. We do so by critically reviewing the related academic and policy literature and taking stock of how multidimensional poverty indices (MPI) are presently utilized in the process of designing, adopting and evaluating social protection strategies across developing Asia in general, and in the Middle East in particular. The relative pros and cons of the MPI and the proxy means tests (PMT), their respective records of implementation, and the prospects of applying them in tandem are discussed. In conclusion, we assess the policy significance and promise of an approach that integrates MPI and PMT, and discuss whether and under what circumstances, such as approach can be effective in the area of social program targeting and tailoring, particularly in middle-income Asian countries.